Peran Institusi Lokal dalam Pemberdayaan Masyarakat: Studi Pengelolaan Badan Usaha Milik Desa di Pujonkidul Kabupaten Malang - Anny Adhibah; Ustad Mangku Alam; Moh. Aris Munandar (Faculty of Social and Political Sciences, Universitas Muhammadiyah Malang, 2022)
This article discusses the successful development of Badan Usaha Milik Desa (BUMDes) by the Pujonkidul Village Government, Malang Regency. This study is essential because the village is a local institution used as the front line in improving the standard of living and welfare of the community. But at the same time, many villages fail to develop their village potential. By comprehensively understanding the efforts of Pujonkidul Village in developing village potential through BUMDes, this study uses an institutional capacity-building framework with three main dimensions: human resources, organization, and institutional reform. Through the qualitative-case study method, this research shows that the development of BUMDes by the Pujonkidul Village Government begins with developing business units. The growth of BUMDes is noted to involve several elements and stakeholders, such as local communities, local governments, private parties, and the mass media. The four of them were successfully integrated and collaborated in encouraging the development of their business units.